Patis a la luz a plant design - Clemente, Mauro G. (College of Engineering, 1970)
Capacity: 8.16 tons/day -- Land area: 30,000 sq.m. -- Fixed capital investment: 1,229,215.00 -- Operating cost at maximum production: 645,000.00 -- Annual sales at maximum production: 5,464,800.00 -- Pay-off period: 1.1 yrs. -- Maximum annual production: 2,448.0 tons -- Break-even point: 18.0% -- Shutdown point: 8.0%